1995
DOI: 10.1074/jbc.270.52.31151
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Association of Platelet-activating Factor Acetylhydrolase with Lipoprotein (a) in Comparison with Low Density Lipoprotein

Abstract: Paired samples of human Lipoprotein (a) (Lp(a)) and low density lipoprotein (LDL) were assayed for their platelet-activating factor (PAF) acetylhydrolase activity. Lp(a) displayed markedly enhanced PAF acetylhydrolase activity (approximately 7-fold based on equal particle concentrations) in comparison to LDL isolated from the same individual. Lp(a)-associated acetylhydrolase exhibited properties observed for LDL-associated acetylhydrolase as well as for the purified enzyme; significant inhibition was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 44 publications
1
50
0
5
Order By: Relevance
“…22 Furthermore, the LDL radius in the present study was estimated from the density range 1.006 to 1.063 kg/L, thus comprising IDL as well. Although PAF-AH was shown to reside on Lp(a), 30 it remains controversial how strongly PAF-AH activity is associated with Lp(a); recently, it was shown that the fluvastatin-induced decrease of PAF-AH activity in patients with type 2 diabetes was independent of Lp(a). 22 One might speculate how PAF-AH mediates increased CAD risk independently of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, the LDL radius in the present study was estimated from the density range 1.006 to 1.063 kg/L, thus comprising IDL as well. Although PAF-AH was shown to reside on Lp(a), 30 it remains controversial how strongly PAF-AH activity is associated with Lp(a); recently, it was shown that the fluvastatin-induced decrease of PAF-AH activity in patients with type 2 diabetes was independent of Lp(a). 22 One might speculate how PAF-AH mediates increased CAD risk independently of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Finally, the intensity of this band by protein staining ( Figure 3A) was much higher than when revealed by Western blot ( Figure 3B); this observation is inconsistent with the finding that Lp(a) contains a 7-fold higher amount of PAF-AH than LDL. 11 Hence, we concluded that this band of greater than normal-sized LDL was due to small aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…7 This density range was chosen to avoid contamination with lipoprotein(a) [Lp(a)], which is known to have a high amount of PAF-AH. 11 Composition of LDL fractions, including total and free cholesterol, triglyceride, phospholipid, apolipoprotein (apo) B, and NEFA, was determined as described previously. 7 Because ultracentrifugation was reported to promote the displacement of PAF-AH from LDL to HDL or lipoprotein-deficient serum, 12 an alternative method to ultracentrifugation was used.…”
Section: Lipoprotein Isolationmentioning
confidence: 99%
“…Second, based on the observations made in three laboratories, apo(a) partially prevents LDL from undergoing oxidation (4,25,26). Third, Lp(a) has a higher concentration of platelet-activating factor acetylhydrolase than authentic LDL (27), a situation that would promote a decrease rather than accumulation of oxPtdPC. According to this concept, the transport of oxPtdPCs in apo(a) would be dependent on their ability to link to the reactive lysines in KV.…”
Section: Figmentioning
confidence: 99%